Model development and simulation of vehicle suspension system with magneto-rheological damper. Issue 1 (November 2021) - Vaishnav, Sarthak; Paul, Jerry; Deivanathan, R
Abstract: A vehicle suspension system is designed to maintain directional control (road holding) during manoeuvring or braking while supporting the vehicle's weight and provide stability (handling). The structure of a suspension system consists of parts connecting the axle to wheel assembly and the chassis of an automobile, thus supporting engine, transmission system and vehicle load. Suspension system components consist of dampening devices, springs, steering knuckles, ball joints and spindles or axles. It could be designed according to a passive, semi-active or active mode of working. For evaluation, this assembly could be modelled as a spring-mass-damper system. The semi-active suspension system has been modelled with a magneto-rheological damper following the Bingham plastic theory. In this paper, the performance of a passive and a semi-active suspension of a quarter car model are compared by MATLAB simulation. Thus, a better suspension system is found out by simulating with different road conditions.